You have an important message! Evaluating the effectiveness of a text message HIV/AIDS campaign in northwest Uganda - Chib, Arul (2013)
There is a growing evidence of the impact of mobile phones in healthcare (mHealth) service delivery, but more research is needed to determine whether SMS (Short Message Service) -based campaigns are appropriate for developing countries. This pilot study explored the efficacy of a mHealth campaign using SMS as a platform to measure and disseminate HIV/AIDS knowledge and to promote HIV/AIDS testing at clinics in rural Uganda. Over a one-month period, 13 HIV/AIDS quiz questions were sent to 10,000 mobile subscribers. Despite participation incentives, only one-fifth of the mobile subscribers responded to any of the questions. The campaign had proportionately limited success in increasing knowledge levels on a mass scale, and had even less impact on behavior change. Further, the program design may be reinforcing entrenched knowledge gaps. The results suggest that we need to be conservative when considering the potential overall impact of SMS-based programs. However, we recognize the potential of mHealth tools when extended to millions of mobile phone users as part of an integrated health campaign approach. We propose several steps to improve the program design to reach a larger portion of the intended audience and increase campaign effectiveness.